Metabolic syndrome and cardiovascular disease in cancer survivors - Kensuke Ueno; Hidehiro Kaneko; Yuta Suzuki; Akira Okada; Satoshi Matsuoka; Katsuhito Fujiu; Nobuaki Michihata; Taisuke Jo; Norifumi Takeda; Hiroyuki Morita; Kentaro Kamiya; Junya Ako; et al. (Wiley, 2024)
Abstract Background The risk of subsequent cardiovascular disease (CVD) is high in cancer survivors. Although metabolic syndrome is an established risk factor for CVD, its association with cancer survivors has not yet been established. This study aimed to clarify whether metabolic syndrome is associated with subsequent CVD risk in patients with cancer using a nationwide epidemiological dataset. Methods We retrospectively analysed 53 510 patients with a history of breast, colorectal, or stomach cancer, which is reportedly a major site for developing cancer in Japan. Study participants were categorized into two groups based on the presence of metabolic syndrome, defined using the Japanese criteria (high waist circumference and ≥2 metabolic parameters including elevated blood pressure, elevated triglycerides, reduced high‐density lipoprotein cholesterol, or elevated fasting plasma glucose). The clinical outcomes were collected between 2005 and 2021. The primary endpoint was defined as the composite CVD outcome, including myocardial infarction, angina pectoris, stroke, and heart failure. Results The median patient age was 54 years, and 37.5% of the patients were men. Metabolic syndrome was observed in 5558 (10.4%) patients. Over a mean follow‐up period of 973 ± 791 days, 3085 composite CVD outcomes were recorded. Multivariable Cox regression analyses showed that metabolic syndrome was associated with a greater risk of developing CVD events (HR = 1.29, 95% CI = 1.15-1.45). Metabolic syndrome was also associated with an increased risk of CVD in patients with a follow‐up period ≥1 year (HR = 1.33, 95% CI = 1.15-1.53). This relationship was also observed when metabolic syndrome was defined according to the International Diabetes Federation criteria (HR = 1.34, 95% CI = 1.21-1.49) and the National Cholesterol Education Program Adult Treatment Panel III criteria (HR = 1.32, 95% CI = 1.19-1.46). Subgroup analyses showed that the relationship between metabolic syndrome and incident CVD was more pronounced in the non‐obese participants than in the obese participants. Conclusions Metabolic syndrome is associated with a greater risk of developing CVD, even among cancer survivors.